Kapabilitas Wirausaha Pemerintah Daerah Dalam Pengelolaan Badan Usaha Milik Desa (BUMDes) di Kabupaten Bintan: - - Afrizal, Afrizal (Jurnal Dialektika Politik, 2024)
The Indonesian government's efforts to realize community welfare start from village communities. Villages are the front yard of the country and a top priority for the government to achieve national development. Village-Owned Enterprises (BUMDes) are one of the government's main programs to improve the economy of village communities. Strengthening the economy of village communities through BUMDes must be followed by strengthening the capabilities of local governments. The ability to balance the capabilities of local government with the economic needs of village communities must be the basis for strengthening the position of BUMDes so that they are able to provide an economic impact for village communities. This research aims to analyze the capabilities of the local government of Bintan Regency in managing BUMDes in Bintan Regency, especially BUMDes in the advanced category, namely BUMDes in Teluk Sasah Village, Ekang Anculai Village and Kampung Hilir Village in managing BUMDes to improve the economy of village communities. This research uses a qualitative approach with interview and observation data collection methods. The results of this research show that local government capabilities have a significant impact on the success of BUMDes in improving the economy of village communities, especially entrepreneurial capabilities. However, on the other hand, entrepreneurial capability cannot be optimized properly, this is due to several factors such as the human resources of the Village Government and BUMDes Managers being still low and the lack of community participation and implementing the BUMDes program.